New Media Literature: An Effort to Combat the Covid-19 Vaccine Hoax in Indonesia - Dewi Udhany; Sylvia Sylvia (Budapest International Research and Critics University, 2022)
The mass media are often accused of being a source of spreading false news (hoax). This often happens especially in new media types (the internet). When the media or individuals put aside the truth of the news to catch up with the speed of news publication or create sensational titles to attract visitors when the reality is completely different. This study is based on the theory of social judgment (Social Judgment Theory), which is part of communication theory that describes and describes how individuals assess messages that begin when reading, listening or responding to a message. This research is a qualitative research that is library research that uses books and other literatures as the main object in Indonesian society. One way to deal with hoaxes, especially in terms of receiving the Covid-19 vaccine, is media literacy. There are seven skills needed to achieve critical awareness of media, including; Ability to analyze, evaluate, group (grouping), message induction, message deduction, message synthesis and make accurate descriptions. The high wave of Covid-19 vaccine hoaxes requires the awareness of the Indonesian people to be observant in filtering information so as to provide social change in vaccination behavior.